Etika Kerja Islam dan Komitmen Adektif Pegawai Negeri Sipil - Rahma Nur Firtriana; Erika S. Kusumaputri (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2014)
The purpose ofthis study was to determine the relationship between Islamic Work Ethics and Affective Commitment. This research was conducted at a state university in Yogyakarta, and involved 103 subjects. The subjects were the employees who work at the university with following the characteristics aged 34-60years and have a service life of 2-10 years. The data was collected using a questionnaire, Islamic Work Ethic scale based on the theory of Ali J. Abbas and Affective Commitment scale based on the theory of Allen and Meyer. The data was analyzed using pearson product moment. The results indicate that there is a positive relationship between Islamic Work Ethics Affective commitment to the value of rxy = 0.459, p < 0.05 . These result indicate that this hypothesis can be accepted, is there is positive between Islamic Work Ethics and Affective Commitment, which means the higher the Islamic Work Ethics that employees have, the higher the Affective Commitment owned by an employee. Keywords: Islamic Work Ethic, Affective Commitment